Resistance and genotype characterization of foodborne Staphylococcus aureus in China - LI Hui; YAN Lin; CHEN Weiwei; XUE Chengyu; YANG Zushun; YANG Dajin; BAI Li (Zhongguo shipin weisheng zazhi, 2023)
ObjectiveTo explore the characteristics of resistance， virulence factor and sequence typing of foodborne Staphylococcus aureus （S. aureus） in China in 2020.MethodsAntimicrobial susceptibility test for S. aureus was performed using the broth microdilution method. Multilocus sequence typing （MLST）， the important antibiotic resistance gene mecA， and virulence genes were analyzed using whole genome sequencing.ResultsThe overall resistance rate of the 224 foodborne S. aureus isolates to 12 classes of antimicrobials was 87.9% （197/224）， with the highest resistance rate of 82.6% （185/224） to penicillin. The multi-drug resistance rate was 23.2% （52/224）， with ST398 accounting for the highest percentage （26.9%， 14/52） of multi-drug resistant bacteria. The methicillin-resistant S. aureus detection rate was 8.0% （18/224）. The overall carriage rate of staphylococcal enterotoxin genes was 52.2% （117/224）， with sea having the highest carriage rate of 24.6% （55/224）. The ST type of S. aureus carrying the most types of enterotoxin genes was ST1. A total of 31 ST types were detected in this study， among which ST7 （12.9%， 29/224） was the predominant ST of isolates， followed by ST398 （10.7%， 24/224）. In addition， the carriage rates of toxic shock syndrome toxin coding gene （tsst-1） and leukocytocin encoding genes （lukF-PV and lukS-PV） were 6.3% （14/224） and 4.5% （10/224）， respectively.ConclusionThe high rate of antimicrobial resistance and enterotoxin genes carriage of foodborne S. aureus in China and the detection of virulence genes that play an important role in clinical infection suggest that the potential hazards of S. aureus in food should not be ignored. There is a high correlation between ST type and food type， antimicrobial susceptibility， and pathogenicity， which provides scientific data for further analysis of the epidemiological characteristics and risk prevention and control of foodborne S. aureus in China.